Development of Learning Concepts For Natural Resources Materials Teaching In High School Students - Evi Apriana; Azwir Azwir; samsul bahri; M Husin (JURNAL SERAMBI ILMU, 2022)
AbstractThis study aims to determine how the development of learning the conceptof conserving biological natural resources (SDAH) in high school studentsthrough a community science technology approach (STS) with a roleplaying method. This research is qualitative in nature, an analysis of the development of learning the concept of conservation of natural resources iscarried out through the STS approach with a role-playing method related toAceh's environmental issues. A trial was conducted on a limited scale on theimplementation of learning in class X-4 with 34 students as a subject in oneof the State Senior High Schools in Darul Imarah District, Aceh BesarDistrict. Data were collected by classroom observation, interviews andconcept understanding tests. The results showed that the development oflearning the concept of conservation of SDAH can be done through the STSapproach with the role playing method, can increase students' motivation,creativity in learning; By playing a role, students can place themselves as ifthey were in a real situation so that they can instill roles, understandconcepts, can improve science and technology for the preservation of livingnatural resources related to Aceh's environmental issues.